Diagnostic Accuracy of Ultrasound for the Directionality of Testicular Rotation and the Degree of Spermatic Cord Twist in Pediatric Patients With Testicular Torsion. (3rd July 2019) - Hosokawa, Takahiro; Takahashi, Hiroaki; Tanami, Yutaka; Sato, Yumiko; Ishimaru, Tetsuya; Tanaka, Yujiro; Kawashima, Hiroshi; Oguma, Eiji; Yamada, Yoshitake
Abstract : Objectives: To evaluate the diagnostic accuracy of ultrasound (US) to diagnose the directionality of testicular rotation and the degree of spermatic cord twist in pediatric patients with testicular torsion. Methods: A retrospective review of 14 pediatric patients with testicular torsion was conducted. The directionality of testicular rotation was classified as an inner or outer direction (inner, counterclockwise in the left testis [viewed from below] and clockwise in the right testis; and outer, counterclockwise in the right testis and clockwise in the left testis). The Clopper‐Pearson method and the Fisher exact, Mann‐Whitney U, and Wilcoxon signed rank sum tests were used for the statistical analyses. Results: The diagnostic accuracy of US in the directionality of testicular rotation and the degree of spermatic cord twist were 78.6% (11 of 14; 95% confidence interval, 49.2%–95.3%) and 36.4% (4 of 11; 95% confidence interval, 10.9%–69.2%), respectively. Outer rotation was seen in 50.0% of the cases. The directionality of testicular rotation and the degree of spermatic cord twist as determined by US were not significantly different between the patients with salvaged testis and those with testicular loss (inner/outer direction, 4/2 versus 4/4; P = .627; mean twist ± SD, 330.0° ± 73.5° versus 337.5° ± 115.4°; P > .999). There was no significant difference in the degree of spermatic cord twist determined by US and surgical results (343.0° ± 97.1° versus 458.2° ± 168.2°; P = .063). Conclusions: The accuracy of US in determining the directionality of testicular rotation was relatively high in our small cohort. This information may be useful for pediatric surgeons and urologists when performing early manual reduction for testicular torsion.